Intellectual Capital and Financial Performance: Comparison With Financial and Pharmaceutical Industries in Vietnam - Zhang, Xiao-Bing; Duc, Tran Phuong; Burgos Mutuc, Eugene; Tsai, Fu-Sheng (Frontiers in Psychology, 2021)
This study investigates the impacts of intellectual capital (IC) and its components: human capital and structural capital on financial performance. In addition, this study compares the effects between firms from financial and pharmaceutical industries. A total of 149 Vietnamese firms comprising of 108 financial firms and 41 pharmaceutical firms were examined. Based on the findings, VAIC and HCE show beneficial impacts on both financial performance measures, ROA and ROE. However, SCE shows adverse and beneficial implications on ROA and ROE, respectively. In terms of industry comparison, VAIC has positive effects on ROA and ROE among the firms from financial industry, whereas it has no effect in the firms from pharmaceutical industry. The effect of HCE on ROA is stronger in the firms from financial industry than firms from pharmaceutical industry while the effect of HCE on ROE is stronger in the firms from pharmaceutical industry than firms from financial industry. The effect of SCE on ROA is stronger in the pharmaceutical firms than financial firms while the effect of SCE on ROE is stronger in the financial firms than pharmaceutical firms. Lastly, the implications of the importance of knowledge-based resources on value creation were elaborated.